2017
DOI: 10.3389/fcimb.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

A Helicobacter pylori Homolog of Eukaryotic Flotillin Is Involved in Cholesterol Accumulation, Epithelial Cell Responses and Host Colonization

Abstract: The human pathogen Helicobacter pylori acquires cholesterol from membrane raft domains in eukaryotic cells, commonly known as “lipid rafts.” Incorporation of this cholesterol into the H. pylori cell membrane allows the bacterium to avoid clearance by the host immune system and to resist the effects of antibiotics and antimicrobial peptides. The presence of cholesterol in H. pylori bacteria suggested that this pathogen may have cholesterol-enriched domains within its membrane. Consistent with this suggestion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(95 reference statements)
0
24
0
1
Order By: Relevance
“…B. burgdorferi and Helicobacter pylori incorporate host cholesterol (Crowley et al ., ; Correia et al ., ) and through the action of a galactose and a glucose transferase, respectively (Lebrun et al ., ; Ostberg et al ., ), make cholesterol glycolipids (Hirai et al ., ). In B. burgdorferi , one of these cholesterol glycolipids, cholesteryl 6‐O‐palmitoyl‐β‐ d ‐galactopyranoside (ACGal), is essential in the formation of lipid rafts (Huang et al ., ), and a recent study detected a flotillin homolog enriched in detergent resistant membranes (DRM), suggesting the presence of lipid rafts in H. pylori (Hutton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…B. burgdorferi and Helicobacter pylori incorporate host cholesterol (Crowley et al ., ; Correia et al ., ) and through the action of a galactose and a glucose transferase, respectively (Lebrun et al ., ; Ostberg et al ., ), make cholesterol glycolipids (Hirai et al ., ). In B. burgdorferi , one of these cholesterol glycolipids, cholesteryl 6‐O‐palmitoyl‐β‐ d ‐galactopyranoside (ACGal), is essential in the formation of lipid rafts (Huang et al ., ), and a recent study detected a flotillin homolog enriched in detergent resistant membranes (DRM), suggesting the presence of lipid rafts in H. pylori (Hutton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The main limitation of this method is that we were unable to generate mutants in the mouse‐colonizing H pylori SS1 and PMSS1 strains, and although kanamycin‐sensitive and 2‐DOG‐resistant colonies could be isolated, they did not contain the desired mutations (data not shown). It is generally known that SS1 and PMSS1 are not as easily amenable to genetic manipulation as other H pylori strains . Nevertheless, given that antibiotic‐resistant and 2‐DOG‐resistant colonies were isolated, it is likely that, with further optimization, this method may be used to generate mutants in this and other less genetically tractable strains .…”
Section: Discussionmentioning
confidence: 99%
“…Although many H pylori genes have been characterized by cloning and expression in laboratory E coli strains, expression of some H pylori proteins can be deleterious to E coli and so prevents their characterization. Traditional methods for H pylori mutagenesis often involve multiple cloning steps, which precede transformation with donor DNA to generate mutants marked with an antibiotic resistance cassette at the target loci . However, integration of an antibiotic resistance cassette introduces pitfalls to subsequent phenotypic analysis of isolated mutants as antibiotic resistance determinants can introduce polar effects on downstream gene expression .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the absence of FLOT reduced the cell scattering output which is mainly attributed to CagA. In vivo experiments showed the absence of FLOT reduced H. pylori colonization in the mice model …”
Section: Virulence Factorsmentioning
confidence: 96%
“…Flolitin‐like protein is described as a membrane raft–associated protein . Protein analysis revealed that FLOT is located in the membrane.…”
Section: Virulence Factorsmentioning
confidence: 99%